Business research methods - Cooper, Donald R.; Schindler, Pamela S. (McGraw-Hill, 2006)
This book offers students and instructors thorough coverage of business research topics backed by solid theory. The authors are successful marketing research consultants and that is evident in the rich and realistic case studies found in the text. Managerial decision making is the underlying theme, while topics and applications are presented and organized in a manner that allow students to thoroughly understand business research topics and functions. Consequently, the structure of the text encourages and supports completion of an in-depth business research project during the semester.